Combating Polio Vaccine Hesitancy: An Evaluation of Mediated Polio Eradication Campaigns in Pakistan - Durre, Durre Shehwar; Dr. Bakht Rawan, (Journal of Peace, Development and Communication, 2023)
Health campaign initiatives are especially tailored to the needs of their target audience and encourage vaccination adoption for polio eradication. Vaccination resistance, however, remains a serious barrier in Pakistan. The content analysis method was used to examine message appeals and message characteristics used in Pakistan's Polio National Immunization Campaigns from 2020 to 2022. Polio advertisements were obtained from the Pakistan Polio Eradication Program's internet archives. Advertisements range in duration from 40 to 60 seconds on average. The quantitative results provided to a deeper understanding of the message characteristics (credibility of message presenters, appeals, style, slogan, language) used in anti-polio advertisements broadcasted via cable and television channels during the Polio National Immunization Campaigns. It was evident that attempts were made to effectively engage the target audience via the employment of 31% knowledgeable speakers, a range of message appeals 34%, and a diversity of communication styles 72%. The necessity for ongoing evaluation and improvement of campaign message techniques was highlighted by variations in the use of slogans and regional languages.